Spectroscopic and conductometric studies on the interactions of thionine with anionic and nonionic surfactants - ÇAKIR, NEŞE; CANTÜRK TALMAN, REMZİYE YEŞİM; GÖKTÜRK, SİNEM (WILEY, 2017)
In this study, the interaction of thionine, a cationic dye, with anionic [sodium dodecyl sulphate (SDS), lithium dodecyl sulphate (LiDS), and sodium dodecylbenzene sulphonate (SDBS)], nonionic (Tween 20 and Triton X-100), and binary mixtures of anionic and nonionic surfactants was studied by conductometric and spectrophotometric measurements. The degree of ionisation, the counterion binding parameters, and the equilibrium constants in the premicellar region were obtained from conductivity data. Binding constants of thionine to anionic, nonionic, and mixtures of anionic and nonionic micelles were determined by spectrophotometric measurements. The binding tendency of thionine to anionic micelles followed the order SDBS > SDS > LiDS. The presence of nonionic surfactants increased significantly the binding affinity of thionine to anionic micelles, and the highest binding constant was calculated in the presence of Tween 20. The results obtained from conductometric studies correlated with those obtained from spectroscopic studies. Data concerning dye-surfactant interaction are important for a fundamental understanding of the performance of single and mixed surfactants and for their industrial application.
Keywords: ALKYLTRIMETHYLAMMONIUM BROMIDE SURFACTANTS; SODIUM DODECYL-SULFATE; CATIONIC SURFACTANT; TRITON X-100; AZO-DYES; MICELLES; AGGREGATION; PREMICELLAR; CHLORIDE; BINDING